Prsepsi Masyarakat Terhadap Rantai Pasok Komoditas Unggulan Di Kecamatan Taluditi - Tegar Botutihe; Fitryane Lihawa; Masruroh Masruroh (-, 2026)
This research aims to analyze the community's perception of the supply chain of leading commodities in Taluditi District and to identify the internal and external factors that influence its development. This research is important to conduct considering the still low efficiency of the supply chain, which impacts the added value of agricultural products. The method used is a descriptive qualitative approach with data collection techniques thru in-depth interviews, field observations, and documentation. Informants were determined thru purposive and snowball sampling, including farmers, collectors, distributors, and consumers. Data analysis was conducted using the SWAT method thru IFAS and EFAS. The research results indicate that internally, there are strengths such as the use of superior seeds, high farmer experience, and the presence of active farmer groups. However, there are still weaknesses such as low technology adoption, minimal training, and the absence of product processing, resulting in low product added value. Externally, there are opportunities such as the opening of digital markets, government program support, and the potential for agro-industrial development, but there are also threats like price fluctuations, the dominance of middlemen, and climate change. Overall, the strategic position is in Quadrant I (aggressive), so development is directed toward utilizing strengths to seize opportunities thru value addition, marketing digitalization, and strengthening farmer institutions.